Comprehensive Overview of the Effective Thermal Conductivity for Hydride Materials: Experimental and Modeling Approaches - Gabriele Scarpati; Julián A. Puszkiel; Jan Warfsmann; Fahim Karimi; Elio Jannelli; Claudio Pistidda; Thomas Klassen; Julian Jepsen (Energies)
In metal hydride beds (MHBs), reaction heat transfer often limits the dynamic performance. Heat transfer within the MHB usually involves solid and gas phases. To account for both, an effective thermal conductivity (ETC) is defined. Measuring and predicting the ETC of metal hydride beds is of primary importance when designing hydride-based systems for high dynamics. This review paper presents an integral overview of the experimental and modeling approaches to characterize the ETC in MHBs. The most relevant methods for measuring the ETC of metal hydride beds are described, and the results and scopes are shown. A comprehensive description of the models applied to calculate the ETC of the MHBs under different conditions is developed. Moreover, the effects of operation parameters such as P, T, and composition on the ETC of the presented models are analyzed. Finally, a summary and conclusions about experimental techniques, a historical overview with a classification of the ETC models, a discussion about the needed parameters, and a comparison between ETC experimental and calculated results are provided.